ANALISIS KELAYAKAN INVESTASI TAMBANG NIKEL Studi lahan IUP operasi produksi PT XYZ di Kab. Bombana, Sulawesi Tenggara - , Muhamad Haris; , Dr. Mamduh M. Hanafi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The main objective of the company is to maximize shareholder value, and a company can increase this value by investing in projects that generate revenues greater than the cost of capital. This thesis is a study to examine whether investment in PT. XYZ nickel mining within area of 531.3 ha. located in the District Kabaena would be viable, reviewed from aspects of the financial and non-financial aspects as well. From some non-financial aspects that were studied, including the marketing aspects, technical aspects, environmental aspects, legal aspects, management, and socio-economic aspects, this nickel mining investment is feasible. The financial feasibility analysis using several criteria such as NPV, PBP, IRR, MIRR, and PI. From the results of the calculations and assumptions used, showed that the investment viable. In addition the sensitivity analysis done to determine how much investment can remain profitable in the event of a change of income and inflation. Given this research, it is expected PT. ABC as investors informed all the benefits that can be obtained, and facilitate PT. XYZ with planning, work execution, monitoring, and control.